Pengaruh Hard Skill, Soft Skill dan Self-Efficacy Terhadap Kesiapan Kerja (Studi Kasus Pada Mahasiswa Tingkat Akhir Universitas PGRI Semarang) - Dhea Novita; Qristin Violinda; M. Fadjar Darmaputra (Journal Economic Excellence Ibnu Sina, 2023)
This research aims to determine the influence of hard skills, soft skills and self-ability on the work readiness of final year students at PGRI Semarang University. This research uses a probability sampling technique research method with a purposive sampling method. Data processing used the SPSS version 25 program. The population used in this research were final semester students at PGRI University Semarang and the sample used was 100 respondents from various study programs at UPGRIS. Primary data by distributing questionnaires via Google Form. The results of the analysis and discussion show that there is a positive and significant influence between the Hard Skill variable (X1) on the Work Readiness variable (Y) partially, with tcount 2.550 > ttable 1.984 with a significance level of 0.012 < 0.05. There is a positive and significant influence between the Soft Skill variable (X2) on the Work Readiness variable (Y) partially, with tcount 4.472 > ttable 1.984 with a significance level of 0.000 < 0.05. There is a positive and significant influence between the Self-Efficacy (X3) and Work Readiness (Y) variables partially, with tcount 5.448 > ttable 1.984 with a significance level of 0.000 < 0.05.